2012
DOI: 10.1590/s1809-29502012000300006
|View full text |Cite
|
Sign up to set email alerts
|

Efeito agudo do calçado de diferentes alturas sobre o comportamento angular do tornozelo

Abstract: Estudos descrevem que o uso de salto alto exige do corpo uma série de ajustes compensatórios, a fim de manter os seus movimentos e equilíbrio próximos à normalidade. No andar, a interferência do salto alto sobre o pé e sobre a articulação do tornozelo parece desencadear uma postura diferente da posição anatômica. O presente estudo teve como objetivos comparar a cinemática sagital do tornozelo em diferentes calçados e verificar a existência de um limite de altura de salto que possa levar a articulação do tornoz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…It was found in the literature that, when measuring one's posture wearing stiletto and platform heels via computerized photogrammetry, there was a difference in knee alignment between the stilettos and bare feet, and in the positioning of the ankle in all footwear evaluated 20 . Limana et al (2012) 21 compared ankle kinematics in different footwear and found that, with increasing heel height, there is an increase in ankle angle during plantar flexion in gait.…”
Section: Discussionmentioning
confidence: 99%
“…It was found in the literature that, when measuring one's posture wearing stiletto and platform heels via computerized photogrammetry, there was a difference in knee alignment between the stilettos and bare feet, and in the positioning of the ankle in all footwear evaluated 20 . Limana et al (2012) 21 compared ankle kinematics in different footwear and found that, with increasing heel height, there is an increase in ankle angle during plantar flexion in gait.…”
Section: Discussionmentioning
confidence: 99%